Efektivitas Komite Audit sebagai Pemoderasi Pengaruh Profitabilitas dan Audit Tenure Terhadap Audit Report Lag - Retnowati, Wulan; Firdaus, Annisya Nurul; Satibi, M (Prodi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas PGRI Madiun, 2024)
This research aims to examine audit report lag, consists of two independent variables: profitability and audit tenure. The dependent variable is audit report lag, and the moderating variable is audit committee effectiveness. This quantitative research utilizes secondary data from financial reports and annual accessible through the Indonesia Stock Exchange (BEI). The population for this study consists mining state-owned companies listed on the BEI from 2012 to 2022. The sampling method applied was purposive sampling, resulting in 4 mining sector state-owned companies being sampled for eleven consecutive years, with a total of 44 observations. Data processing was carried out using SPSS (Statistical Product and Service Solutions) version 25. The data analysis technique used was moderated regression (MRA). The research results show that profitability has no effect, while the audit tenure has a significant negative effect, and audit committee effectiveness has a moderating effect on the effect of profitability and audit period on audit report lag